Obstetrical Management of an Extremely Overweight Pregnant Woman (184 kg bw) with Special Attention on Thromboprophylaxis. (4th March 2013) - Horváth, Boldizsar; Skrapits, Judit; Bódis, József
Abstract : The 27-year-old pregnant woman has been overweight since her childhood. Endocrinological assessments did not confirm hormonal disease. Her pregnancy was without complication. A signs of intrauterine distress were observed and elective caesarean section was performed under heparin protection because of anatomy unsuitable for delivery per vias naturals. The mother's bodyweight was 184 kg. By monitoring the change in fX activity LMWH treatment (Enoxaparin) initiated with a dose of 120 mg twice daily and then the dose was gradually elevated to 200 mg twice daily thereby achieving the lower range of the desired therapeutic effect. Apart from mild disorder of wound healing, the recovery was free of complication. The patient suffered from thrombophilia (extremely overweight, pregnant, thrombophlebitis under the knee, surgery, and postoperative immobilization). In case of quite extreme bodyweight there is no dosage recommendation or clinical practice for LMWH. Because of the extreme overweight and the therapeutic dose titration test of heparin, monitoring of fX activity by measurement of inhibition, dosage of heparin other than the recommended (abdominal wall instead of upper arm SC), and the very fluctuating heparin dosage which is well correlating with clinical practice, it is reasonably expected that this case will take interest.